Impact of national e-commerce demonstration city pilot policy on urban carbon emission efficiency: From the perspective of soft and hard environments - YUE Li, WANG Xinran (Ziyuan Kexue)
[Objective] This study aimed to assess the impact of the national e-commerce demonstration cities (NEDC) pilot policy on urban carbon emission efficiency (CEE) and its underlying mechanisms. It focused on the moderating effects of e-commerce soft and hard environments, providing policy references for achieving carbon neutrality and peak carbon emissions goals. [Methods] Based on prior research, this study employed multiple-period difference-in-differences and double machine learning models to rigorously identify the causal relationship between the NEDC pilot policy and urban CEE, using panel data of 282 prefecture-level administrative units in China from 2006 to 2022. The analysis integrated the internal mechanisms of the pilot policy’s impact on CEE from supply and demand sides. This study constructed a comprehensive evaluation system of e-commerce soft and hard environments to access their moderating effects on the policy’s impact. [Results] The empirical findings reveal that the NEDC pilot policy significantly promoted urban CEE, with robust results verified through endogeneity test and multiple robustness tests. Both soft and hard environments demonstrated positive moderating effects on the policy’s impact on CEE, where network and logistics infrastructure in the hard environment played a crucial role, while technological innovation, governmental regulation and market environment in the soft environment exhibited strong moderating effects. Furthermore, the policy’s impact exhibited heterogeneity, with more pronounced effects in non-resource cities, growth-regenerative cities, and cities with higher levels of international trade. [Conclusion] To promote policy-enabled CEE, the carbon reduction effect of the pilot policy should be strengthened at both supply and demand sides. The soft and hard environments of e-commerce should be further optimized. It is recommended to advance the construction of pilot cities in an orderly manner, establish industrial e-commerce ecosystem, reinforce the coordinated optimization of soft and hard environments, and develop e-commerce according to local conditions.